Nonstructural protein NS17 of grass carp reovirus Honghu strain promotes virus infection by mediating cell-cell fusion and apoptosis - Yanlin Dai; Yiqun Li; Xi Hu; Nan Jiang; Wenzhi Liu; Yan Meng; Yong Zhou; Chen Xu; Mingyang Xue; Yuding Fan (Virus Research, 2023)
Fusion-associated small transmembrane (FAST) proteins can promote cell fusion, alter membrane permeability and trigger apoptosis to promote virus proliferation in orthoreoviruses. However, it is unknown whether FAST proteins perform these functions in aquareoviruses (AqRVs). Non-structural protein 17 (NS17) carried by grass carp reovirus Honghu strain (GCRV-HH196) belongs to the FAST protein family, and we preliminarily explored its relevance to virus infection. NS17 has similar domains to FAST protein NS16 of GCRV-873, comprising a transmembrane domain, a polybasic cluster, a hydrophobic patch and a polyproline motif. It was observed in the cytoplasm and the cell membrane. Overexpression of NS17 enhanced the efficiency of cell-cell fusion induced by GCRV-HH196 and promoted virus replication. Overexpression of NS17 also led to DNA fragmentation and reactive oxygen species (ROS) accumulation, and it triggered apoptosis. The findings illuminate the functions of NS17 in GCRV infection, and provide a reference for the development of novel antiviral strategies.